Chendol-Chendolan Trader / Mohd Shahari Saidali ... [et al.] - Saidali, Mohd. Shahari; Nurdin, Aydil Fazni; Mohd Sarip, Mohd. Sadre; Munir, Zulhilmi; Amat Javavi, Mohd. Fakhruddin (2011)
Chendolan- Chendolan Trader is a new set up manufacturing firm that manufacture very own cendol. The specialities of Chendol-Chendolan Trader are selling variety of cendol and operate the business in the concept of mobile concept. Chendol-Chendolan trader is scheduled to begin the operations on January 2, 2012. Chendol-Chendolan will be partnerships which are consist of five partners. There are consist of Mohd Shahari bin Saidali, Aydil Fazni bin Nurdin, Mohd Sadre bin Mohd Sarip, Zulhilmi bin Munir and Mohd Fakhruddin bin Amat Javavi Location of office for the Chendolan-Chendolan Trader will be at the Alamesra and for the operating location will be five different areas which are Indah Permai, Tanjung aru, Gaya Street, Jalan Punat Tanah and KPD. Chendol-Chendolan Trader will target their market specific in the Kota Kinabalu. Chendol-Chendolan Trader will divide their target market based on geodemographic segmentation. This segmentation consist of students, household and local visitors. In term of market size, Chendol-Chendolan Trader estimated 15% of the 205,000 will be potential customers. Market strategies of Chendol-Chendolan Trader will be implementing 4P concepts which are product, pricing, promotion and place strategy. For the operating plan, Chendol-chendolan trader will start operates from 10am until 6 pm from Monday to Thursday and from 8am until 6pm on Saturday and Sunday. Chendol- Chendoalan will provide variety taste of cendol that will serve to the customer. For the starting of the business, Chendol-Chendolan Trader will prepare five types of taste. There are consist of 'cendol milo', 'cendol aiskrim', 'cendol fruit cocktail', 'cendol smarties' and 'cendol longan'.